Modeling plasticity of an aluminum 2024T351 thick rolled plate for cold forming applications. (1st October 2020) - Cusset, Raphaël; Azzouz, Farida; Besson, Jacques; Dragon-Louiset, Marta; Jacques, Vincent; Proudhon, Henry
Abstract: Sheet metals exhibits plastic anisotropy due to the rolling process. This article focuses on the particular case of an 2024T351 Aluminium alloy thick sheet which showed in addition to the anisotropy of mechanical properties an important evolution of the these properties along the thickness. A large series of tension tests performed is carried out using samples machined varying the position along the thickness and the orientation in the rolling plane. Strong variation in terms of elastic limit and ultimate tensile stress are observed. The heterogeneity of the miscrostructure is studied by EBSD along the plate thickness and correlated with the mechanical properties variations; 4 main zones are identified. The constitutive behaviour of the material is model using an anisotropic yield criterion combined to a non-linear hardening rule and one set of parameters is identified for each material layer. The predictive capabilities of the model are illustrated by simulations of notched tension tests with three notch radii. Finally a large structure panel bending test representative of cold forming industrial operations is simulated using the identified model parameters. A very good agreement between the FE results and the experimental strain gauge signals from a scale 1 experiment is observed. This shows the thickness-based identification accurately account for the property gradient for large structure panel simulations.